Analysis of high and selective uptake of CO2 in an oxamide-containing {Cu2(OOCR)4}-based metal-organic framework - Alsmail, Nada H.; Suyetin, Mikhail; Yan, Yong; Cabot, Rafel; Krap, Christina P.; Lü, Jian; Easun, Timothy L.; Biskoutskaia, Elena; Lewis, William; Blake, Alexander J.; Schröder, Martin (Wiley-VCH Verlag, 2014)
The porous framework [Cu2(H2O)2L].4H2O.2DMA ((H¬4¬L = oxalylbis(azanediyl)diisophthalic acid; DMA = N,N-dimethylacetamide), denoted NOTT-125, is formed by connection of {Cu2(RCOO)4} paddlewheels with the isophthalate linkers in L4-. A single crystal structure determination reveals that NOTT-125 crystallises in monoclinic cell with a = 27.9161(6) Å, b = 18.6627(4) Å and c = 32.3643(8) Å, space group P2 (1)/c. The structure of this material shows fof topology, which can be viewed as the packing of two types of cages (Cage A and Cage B) in 3-dimensional space. Cage A is constructed by twelve {Cu2(OOCR)4} paddlewheels and six linkers to form an ellipsoid-shaped cavity approximately 24.0 Å along its long axis and 9.6 Å across the central diameter. Cage B consists of six {Cu2(OOCR)4} units and twelve linkers with a spherical diameter of 12.7 Å taking into account the van der Waals radii of the atoms. NOTT-125 incorporates oxamide functionality within the pore walls, and this, combined with high porosity in the desolvated NOTT-125a, is responsible for excellent CO2 uptake (40.1 wt% at 273 K and 1 bar) and selectivity for CO2 over CH4 or N2. Grand canonical Monte Carlo (GCMC) simulations show excellent agreement with the experimental gas isotherm data, and a computational study into the specific interactions and binding energies of both CO2 and CH4 with the linkers in NOTT-125 reveals a set of strong interactions between CO2 and the oxamide motif, which are not possible with a single amide.